The correlates of anal intercourse among male sex workers in the cities of Quezon and Manila, Philippines - Ho Van Bao.
To determine the types of anal intercourse and the correlates of anal intercourse among male sex workers in the cities of Quezon and Manila, Philippines.This is a secondary analysis of a survey on the HIV/AIDS related risk profile of Filipino male sex workers composed of 679 male sex workers from the cities of Quezon and Manila. The major outcome was the practice of anal intercourse. Three exposure variables including sexual orientation, number of clients and types of non-paying sexual partner were determined in the association with the practice of anal intercourse.Thirty eight percent (37.7) reported having anal intercourse during the last two weeks. Of these, 31.4had engaged in insertive anal intercourse only 1.8in the receptive role. The subjects were mostly self-identified as heterosexual (80.2) and had a median of 3 clients per week. The majority (61.1) had no sexual partners and 28.1had only female partners. The inferential analsis has shown the association between AI and sexual orientation and the number of clients. Homosexuals/bisexuals who had no non-paying sexual partners were more likely to engage in AI than heterosexual (OR = 2.27; 95CI = 1.35 - 3.81). Among those who self-identified as heterosexuals, those who had non-paying male sexual partners were more prone to engage in AI (OR = 4.58; 95CI = 1.71 - 12.22) Among the non-drinkers of alcohol, those who had more than two clients per week were more likely to engage in AI.Prevention strategies should be strengthened to maintain and reduce this high-risk sexual behavior. The subpopulation of homosexual/bisexuals among MSWs should be targeted for the prevention of AI. Further, education programs need to emphasize this behavior practiced by MSWs who tend to have many clients.
Thesis (Master of Science in Epidemiology)--University of the Philippines Manila.
Keywords: Anal sex; Male prostitutes